Phragmites australis + Typha latifolia Community Enhanced the Enrichment of Nitrogen and Phosphorus in the Soil of Qin Lake Wetland. (19th February 2017) - Ge, Zhiwei; An, Ran; Fang, Shuiyuan; Lin, Pengpeng; Li, Chuan; Xue, Jianhui; Yu, Shuiqiang
Abstract : Aquatic plants play an essential role and are effective in mitigating lake eutrophication by forming complex plant-soil system and retaining total nitrogen (TN) and phosphorus (TP) in soils to ultimately reduce their quantities in aquatic systems. Two main vegetation types ( Phragmites australis community and P. australis + Typha latifolia community) of Qin Lake wetland were sampled in this study for the analysis of TN and TP contents and reserves in the wetland soils. The results showed that (1) the consumption effect of Qin Lake wetland on soluble N was much more significant than on soluble P. (2) The efficiency of TN enrichment in wetland soil was enhanced by vegetation covering of P. australis and T. latifolia . (3) Wetland soil P was consumed by P. australis community and this pattern was relieved with the introduction of T. latifolia . (4) According to the grey relativity analysis, the most intensive interaction between plants and soil occurred in summer. In addition, the exchange of N in soil-vegetation system primarily occurred in the 0–15 cm soil layer. Our results indicated that vegetation covering was essential to the enrichment of TN and TP, referring to the biology-related fixation in the wetland soil.